(untitled) (International relations and international law Journal, 2020)
At the beginning of the XXI century, the Central Asian region became one of the most important geopolitical centers of the modern world. Before starting to analyze the current position of the Central Asian States in the world political system, it is necessary to determine the geopolitical framework of this concept. The problem of regionalization of the “Central Asian region” phenomenon is still relevant. Increasing the importance of regions in the system of international relations in the twenty-FIRST century from the point of view of international security, positively increases the importance of the “Central Asia” region in Eurasia.The article analyzes the role of “ Central Asia “in the system of international relations based on the concepts of “Central Asia”,” post-Soviet Asia”,”Greater Central Asia”,”heartland”. The article analyses the importance of Central Asian region in the world political system. The Central Asian region has become one of the most important geopolitical centers of the modern world. The geopolitical role of the region is determined by its intercontinental significance for trade and other relations between the countries of Europe, the Middle East and Asia. The history of the region’s geopolitical development is analyzed as the main scientific method. In Central Asia, the political role of each participant in the region is analyzed based on the conceptual analysis of the data accumulated by reviewing the literature, a scientific analysis and the necessary conclusions are made.